Psychological and Psychopharmacological Interventions in Psychocardiology - Kai G. Kahl; Britta Stapel; Christoph U. Correll; Christoph U. Correll; Christoph U. Correll (Frontiers in Psychiatry, 2022)
Patients with mental disorders have an increased risk to develop cardiovascular disease (CVD), and CVD are frequently comorbid with especially adjustment, anxiety and depressive disorders. Therefore, clinicians need to be aware of effective and safe psychological and pharmacological treatment strategies for patients with comorbid CVD and mental disorders. Cognitive behavioral therapy and third-wave of cognitive-behavioral therapy are effective for patients with CVD and mental disorders. Internet-based psychological treatments may also be considered. In more severe cases, psychopharmacological drugs are frequently used. Although generally well tolerated and efficacious, drug- and dose-dependent side effects require consideration. Among antidepressants, selective serotonin reuptake inhibitors, selective serotonin and noradrenalin reuptake inhibitors, and newer antidepressants, such as mirtazapine, bupropion, agomelatine, and vortioxetine, can be considered, while tricyclic antidepressants should be avoided due to their cardiac side effects. Mood stabilizers have been associated with arrhythmias, and some first- and second-generation antipsychotics can increase QTc and metabolic side effects, although substantial differences exist between drugs. Benzodiazepines are generally safe in patients with CVD when administered short-term, and may mitigate symptoms of acute coronary syndrome. Laboratory and ECG monitoring is always recommended in psychopharmacological drug-treated patients with CVD. Presence of a heart disease should not exclude patients from necessary interventions, but may require careful risk-benefit evaluations. Effectively and safely addressing mental disorders in patients with CVD helps to improve both conditions. Since CVD increase the risk for mental disorders and vice versa, care providers need to screen for these common comorbidities to comprehensively address the patients’ needs.